Representações sociais de universitários sobre a comissão nacional da verdade - Albuquerque, Rosiane Alves de (2016)
This master thesis is the result of an empirical study located in the field of transitional justice, more specifically, the Truth Commissions (TC), the Social Representations and Human Rights (HR). More broadly, this work is the inclusion of Brazil in a survey of Latin American countries that have established TCs, such as Chile, Argentina, Ecuador, Paraguay, Peru and Uruguay. The TC is a form of transitional justice, installed after repressive regimes or armed conflict, contributing to the democratic transition of the country. Some objectives of these committees are: knowledge of the truth about what happened, building a collective memory and search for justice from the victims. Introduced in March 2012, the National Truth Commission (NTC) extended its activities by December 2014. Despite the creation of NTC constitute a milestone in the Brazilian history and democracy, psychology as a science and socio-political knowledge has contributed little to the discussion about serious violations of HR occurred in Brazil. This deficit reflects the low production on the subject. Brazil features as one of the last countries in Latin America to set up a TC, considering the time interval between the end of the dictatorship and the establishment of the commission. From the military dictatorship (1964-1985) to the creation of NTC it took 27 years. These data and little social impact of NTC demonstrate the difficulty of Brazilian people in dealing with the past. In the present study, we sought to verify the social representations of College students on the NTC and how these representations were related to corresponding variables to force ideas. Specifically, we sought to investigate the relationship between variables related to forceideas; analyze the relationship between variables corresponding to the Military Dictatorship (MD); check the relationship between strength and ideas variables related to MD; examine the relationship between force-ideas and related variables and NTC; investigate the relationship between variables corresponding to the MD and variables related to NTC. Participants were 252 students of the Center for Humanities of UFPB, located in the Campus I, in João Pessoa/PB, Brazil. The instrument used for data collection consisted of a questionnaire composed of different thematic scales (Degree of exposure to violence; Predisposition to review the past, social sharing on MD and NTC, rating of the work of NTC; violence usage compliance indicators, degree of post-conventionality; Attitudes to HR, institutional trust; basic principles of equality and tolerance, political orientation, etc.), was developed and implemented in other countries (Chile, Argentina, Ecuador, Paraguay, Peru and Uruguay), translated from Spanish to Portuguese and validated semantically. Data analyses were performed using SPSS software. Descriptive analysis, correlation analysis, factor analysis and multiple linear regressions were performed. Among the results we observed that the forceideas - political, ideological and moral aspects -, concepts for Doise, anchored the social representations of NTC and to the approval of the NTC work and positive predisposition to the last review are consistent with the positive attitudes to HR.